Erratum: Pengaruh High Intensity Interval Training Terhadap Kondisi Fisik Pada Atlet Pencak Silat - Sartono Sartono; Firman Adityatama (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.565 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article